Comparative analysis of floc characteristics and microbial communities in anoxic and aerobic suspended growth processes. (21st December 2022) - He, Huanqi; Carlson, Avery L.; Nielsen, Per Halkjær; Zhou, Jizhong; Daigger, Glen T.
Abstract: A fully anoxic suspended growth process is an appealing alternative to conventional activated sludge (AS) due to considerable aeration reduction and improved carbon processing efficiency for biological nutrient removal (BNR). With development of the hybrid membrane aerated biofilm reactor (MABR) technology, implementation of a fully anoxic suspended growth community in BNR facilities became practical. To better understand potential limitations with the elimination of aeration, we carried out microscopic examination and 16S rRNA gene‐based microbial community profiling to determine how an anoxic suspended growth would differ from the conventional aerobic process in floc characteristics, microbial diversity, microbial temporal dynamics, and community assembly pattern. Fewer filamentous populations were found in the anoxic mixed liquor, suggesting easily sheared flocs. The anoxic microbial community had distinct composition and structure, but its diversity and temporal dynamics were similar to the conventional aerobic community. A variety of well‐studied functional guilds were also identified in the anoxic community. The anoxic microbial community assembly was more stochastic than the conventional aerobic community, but deterministic assembly was still significant with a large core microbiome adapted to the anoxic condition. Practitioner Points: Flocs developed under the anoxic conditions had less filamentous backbones, implying reduced flocculation capacity and easily sheared flocs. Knowledge about the ecophysiology of Thauera, Thiothrix, and Trichococcus can help achieve good properties of the anoxic flocs. A diverse microbial community sustainably adapted to the fully anoxic condition, containing a variety of filaments, denitrifiers, and PAOs. The anoxic microbial community displayed a similar degree of diversity and temporal dynamics compared to the aerobic counterpart. The anoxic community's assembly was more stochastic, so it may be less subject to changes in environmental variables. Abstract : This paper investigated that how an anoxic suspended growth process would differ from a conventional aerobic counterpart in floc characteristics, microbial diversity, temporal dynamics, and community assembly processes. We also revealed potential limitations with the elimination of aeration in the suspended growth for the biological nutrient removal processes.